A World Art History and Its Objects - Carrier, David 1944- (Penn State University Press, 2021)
Is writing a world art history possible? Does the history of art as such even exist outside the Western tradition? Is it possible to consider the history of art in a way that is not fundamentally Eurocentric? In this highly readable and provocative book, David Carrier, a philosopher and art historian, does not attempt to write a world art history himself. Rather, he asks the question of how an art history of all cultures could be written-or whether it is even possible to do so. He also engages the political and moral issues raised by the idea of a multicultural art history. Focusing on a consideration of intersecting artistic traditions, Carrier negotiates the way meaning and understanding shift or are altered when a visual object from one culture, for example, is inserted into the visual tradition of another culture. A World Art History and Its Objects proposes the use of temporal narrative as a way to begin to understand a multicultural art history